The Impact of a Community Development and Poverty Reduction Program on Early Childhood Development in Morocco - El-Kogali, Safaa; Krafft, Caroline; Abdelkhalek, Touhami; Benkassmi, Mohamed; Chavez, Monica; Bassett, Lucy; Ejjanoui, Fouzia (World Bank, Washington, DC, 2016)
Participatory community development programs are designed to match government investments with local needs. In Morocco, where issues of inequality and poverty are high on the national agenda, a community development program, the National Initiative for Human Development, targeted high-poverty areas for additional investments. This paper examines whether, in addition to reducing poverty, such programs can also promote human development, specifically early childhood development. Early childhood development forms a critical foundation for later human development and plays a key role in the intergenerational transmission of socioeconomic status. Using panel data on communities just above and below the cutoff for National Initiative for Human Development inclusion in rural areas, regression discontinuity and fixed effect models are applied to identify the impact of the program on economic outcomes and early childhood development. Although the analysis finds some transitory impacts of the program on economic outcomes, it finds no impacts on early childhood development. Reducing inequality and promoting human development through early childhood development is likely to require specific, targeted, and sustained initiatives.